Evaluasi Penjadwalan Proyek Waste Water Treatment Plan Menggunakan Metode Precedence Diagram Method dan Crashing - Renata Alvita Loka Leonsi; Renanda Nia Rachmadita; Aulia Nadia Rachmat (Proceedings Conference On Design Manufacture Engineering And Its Application, 2021)
Scheduling is needed to run the project optimally, efficiently and according to the planned schedule. There are several factors that make the project late. The causes are ineffective working hours, late arrival of materials, and high work productivity. Waste water treatment plan is one of the manyprojects undertaken by PT.Samudra Mas Nusantara. In this project there was a delay of 34 days from the planned duration of 75 days to 109 days. The scheduling method used is the Precedence Diagram Method. The duration of project completion is accelerated by analyzing the acceleration of eachactivity. The s-curve is used to see the progress of the project each week. The results of the research show that there is 1 critical path, namely the path with activities A-B1-B2-C1-C2-D111-D121-D131- D141-D21-D22-D23-D24-D25-E1-E4-F-G-H. The duration of the activity can be accelerated by 35 days from 109 days to 74 days with an increase in costs of 3.03% from Rp.1,822,201,012- up to Rp1,877,287,312,-.